Properties of Polyetheretherketone (PEEK) transferred materials in a PEEK-steel contact - Puhan,D; Wong,J (Tribology International, 2019)
Polyetheretherketone (PEEK) is a high performance polymer that can be an alternative to metal for some moving components in unlubricated conditions. During rubbing, PEEK is transferred to the counterface. The formation and properties of PEEK transfer films on steel and sapphire are studied by in-situ observations of PEEK wear process, contact temperatures and triboemission, as well as FTIR and Raman spectroscopies ex situ. Our results suggest that frictional heating alone may not be sufficient to generate PEEK degradation observed in the transfer materials. Triboplasma observed during rubbing, together with the mechanical shear, may promote generations of radicals and degradation of PEEK, which subsequently influence the properties of PEEK transfer film and performance of polymer-metal tribopair.